Endophilin B1 regulates EGFR endocytic degradation in prostate cancer cell - Zhu, J-Y; Xiong, Y; Zhang, W; Wan, J (Cellular and Molecular Biology, 2016)
Prostate cancer (Pca) is one of the most common types of cancer for elder men. Aberrant expression of epidermal growth factor receptor (EGFR) and EGFR downstream signaling have been known to contribute to disease progression in prostate cancer. EGF-stimulated EGFR is internalized and the process of endocytic degradation of EGFR mediates its signaling which is frequently dysregulated in many kinds of cancer. In the present study, we demonstrated that endophilin B1 expression was inhibited and EGFR expression was significantly increased in prostate cancer cell lines. We demonstrated that suppression of endophilin B1 increased EGFR levels via delaying EGFR internalization triggered by EGF and its intracellular degradation. Endophilin B1 decreased also sustained EGFR downstream signaling such as Erk1/2 phosphorylation in response to EGF stimulation and promoted prostate cancer cell proliferation which is EGF independent. Our data indicated that endophilin B1 mediated the biological function of EGFR in cancer cell proliferation through regulating the EGFR endocytic trafficking and downstream signaling.